Cryo-EM structures of the ATP-bound Vps4E233Q hexamer and its complex with Vta1 at near-atomic resolution - Shan Sun (Nature Portfolio, 2017)
The ESCRT-III and Vps4 complexes mediate a variety of membrane remodelling events. Here the authors describe the structure of the Vps4 hexamer complexed to its cofactor Vta1, and show that Vta1 bridges adjacent Vps4 subunits to promote formation of the active hexamer during ESCRT-III filament disassembly.